Fabrication and characterization of Ag-Sr-substituted hydroxyapatite/chitosan coatings deposited via electrophoretic deposition: A design of experiment study - Saleem, Osama; Wahaj, Muhammad; Akhtar, Muhammad Asim; Rehman, Muhammad Atiq Ur (ACS Omega, 2020)
In this study, silver-strontium-doped hydroxyapatite (AgSr-HA)/chitosan composite coatings were deposited on a 316L stainless steel (SS) substrate via electrophoretic deposition (EPD). The Taguchi design of experiment (DoE) approach was used to optimize the EPD parameters such as the applied voltage, interelectrode spacing, and deposition time. Furthermore, the concentration of AgSr-HA particles in the suspension was also optimized via the DoE approach. DoE results demonstrated that the "homogeneous"coatings were obtained at the deposition time of 7 min, deposition voltage of 20 V, and at a concentration of 5 g/L AgSr-HA particles in the suspension. Scanning electron microscopy (SEM), energy-dispersive X-ray spectroscopy (EDS), antibacterial studies, contact angle, and roughness measurements were performed to characterize the optimized coatings. SEM images confirmed the deposition of chitosan/AgSr-HA on the SS substrate. The wettability studies indicated the hydrophilic nature of the chitosan/AgSr-HA composite coatings, which confirmed that the developed coatings are suitable for biomedical applications, e.g., orthopedics. The average surface roughness of the chitosan/AgSr-HA composite coatings was in a suitable range used to attach the bone marrow stromal cells. Chitosan/AgSr-HA composite coatings showed an effective antibacterial effect against Gram-positive and Gram-negative bacteria. Moreover, the coatings developed apatite crystals on their surface upon immersion in simulated body fluid.
CRIS-Team Scopus Importer:2020-10-16